(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Managing income is a critical component of achieving financial stability and reaching financialgoals. This article provides practical tips for managing income, including creating a budget, trackingexpenses, prioritizing spending, saving for emergencies, investing in the future, avoiding debt, andseeking professional advice. take control of their finances and make informed financial decisions toachieve financial success.